Kontribusi Dukungan Orangtua dan Dukungan Teman terhadap Self Regulated Learning di SLTA A B Yogyakarta - Yuzarion; Prasetya, Akhmad Fajar; Alfaiz (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2023)
Self-regulated learning is the skill of organizing and directing oneself in the process of learning. Every student should possess self-regulated learning skills in order to achieve high academic performance. Various factors influence a student's self-regulated learning during their educational journey. According to social cognitive theory, these factors are the result of the reciprocal interaction between individual characteristics, behavior, and the environment. This research primarily focuses on environmental factors, namely parental support and peer support. Both parental support and peer support play a role in shaping self-regulated learning. The research aims to empirically examine the contribution of parental support and peer support to self-regulated learning. The research employs a quantitative methodology and takes the form of an ex post facto study. The study population consists of 385 students in the 11 grade from SLTA A and B in Yogyakarta. A random sample of 77 students was chosen independently. Data were collected using instruments, including a self-regulated learning scale, a parental support scale, and a peer support scale. The empirical results of the study reveal that both parental support and peer support significantly contribute to self-regulated learning, with an F value of 36.703 and p-value of 0.000 (p<0.01). When examined separately, parental support significantly and positively contributes to self-regulated learning, with a t-value of 2.032 and a p-value of 0.046 (p<0.05). Peer support also significantly and positively contributes to self-regulated learning, with a t-value of 8.325 and a p-value of 0.000 (p<0.01). Partially, parental support contributed 2.79% and friend support contributed 47.01% to self-regulated learning, and the rest was influenced by other factors.